1996
DOI: 10.1161/01.str.27.12.2328
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Smell, Taste, and Food Intake in a Patient With a Dorsomedial Thalamic Infarct

Abstract: This case suggests that the dorsomedial thalamus may play a role in the hedonic perception of food, thus affecting short-term regulation of food intake, and may possibly have a role in the long-term control of body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 13 publications
2
35
1
Order By: Relevance
“…In rodents, ablation of this structure impairs olfactory discrimination learning (Eichenbaum et al, 1980;Slotnick and Kaneko, 1981;Staubli et al, 1987;McBride and Slotnick, 1997), particularly for odors that were unfamiliar or difficult to associate (Eichenbaum et al, 1980), and these deficits are overcome only after extensive training (Staubli et al, 1987). In humans, lesions of the medial thalamus have been associated with odor discrimination impairments (Potter and Butters, 1980) as well as defects in the perception of odor valence (Rousseaux et al, 1996). Notwithstanding the functional complexity of MD thalamus, our results suggest a novel way to unify this body of work: a disruption of sensory attention may best explain the olfactory behavioral impairments documented in thalamus-lesioned animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, ablation of this structure impairs olfactory discrimination learning (Eichenbaum et al, 1980;Slotnick and Kaneko, 1981;Staubli et al, 1987;McBride and Slotnick, 1997), particularly for odors that were unfamiliar or difficult to associate (Eichenbaum et al, 1980), and these deficits are overcome only after extensive training (Staubli et al, 1987). In humans, lesions of the medial thalamus have been associated with odor discrimination impairments (Potter and Butters, 1980) as well as defects in the perception of odor valence (Rousseaux et al, 1996). Notwithstanding the functional complexity of MD thalamus, our results suggest a novel way to unify this body of work: a disruption of sensory attention may best explain the olfactory behavioral impairments documented in thalamus-lesioned animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have generated the view that, in olfaction, the thalamus may subserve higher-order processing (Eichenbaum et al, 1980;Slotnick and Kaneko, 1981;Slotnick and Risser, 1990). Consistent with this view, single-patient case studies suggested that thalamic lesions may spare detection but impair both discrimination (Potter and Butters, 1980) and hedonic judgments of odors (Rousseaux et al, 1996;Asai et al, 2008). In turn, a comprehensive brain imaging study found a thalamic role in olfactory attention (Plailly et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…8,26,27 In a cohort of stroke survivors, 28 24% experienced weight loss of greater than ~6.6 lbs (3 kg). Those identified as having eating difficulties were more likely to experience significant weight loss at 4-month follow-up.…”
Section: Weight Loss and Malnutritionmentioning
confidence: 99%
“…Impaired taste perception can result from lesions in several locations including the pons, insular cortices, and specific thalamic nuclei. [1][2][3][4][5][6][7][8][9][10] Several case reports have detailed altered taste as a result of isolated pontine lesions [2][3][4][5][6]10 as well as both isolated right and left insular lesions. 11,12 Deficits including ageusia (inability to taste), hypogeusia (decreased ability to taste), and dysgeusia (distorted ability to taste) have also been described.…”
mentioning
confidence: 99%